Research Examining the Influence of Sichuan’s Industrial Structure on Economic Growth - Zhang, Kaibo; Tang, Lichao (Journal of Global Economy, Business and Finance, 2025)
As a prominent western province, Sichuan serves as a significant driver of economic growth in the region. This study focuses on 21 cities (prefectures) in Sichuan Province, utilizing urban panel data spanning from 2014 to 2023 to empirically investigate the influence of industrial structure on economic expansion. Our findings reveal that enhancing the industrial structure notably boosts local economic growth. However, its impact exhibits regional variations: it is most pronounced in the Southern Sichuan Economic Zone and the Northwest Sichuan Ecological Demonstration Zone, while having the least effect in the Chengdu Plain Economic Zone. To leverage this understanding, it is recommended to optimize resource allocation to foster coordinated regional development.